'Difficult to imitate and impossible to equal': Byron, Burns, Moore and the Packaging of National Song. Issue 2 (December 2017) - McCue, Kirsteen
Abstract : In the early 1810s, just before embarking on his Hebrew Melodies project, Byron engaged in a correspondence with the Scottish song editor George Thomson (1757–1851). While Byron chose not to engage in Thomson's commission to write lyrics for his collections of Irish and Welsh songs, Thomson nonetheless published a number of Byron's extant lyrics across his collections over the succeeding decades. This article traces how this happened, looks at Thomson's final editorial choices and presentations of Byron's lyrics, and reflects on the role of Byron as national songster alongside Thomson's most significant poetic contributor, Robert Burns, and Byron's great singer/songwriter friend Thomas Moore. 1